SETTING STRATEGY AT FIVE-STAR HOTEL USING VALUE CHAIN ANALYSIS: CASE STUDY ON PT. SARASWATI GRIYA LESTARI, TBK - Muhammad Affan Gaffar; Muhammad Aulia Rahman (AIBPM Publisher, 2018)
The purpose of this research is to discuss about the application of value chain analysis model by using Crain and Abraham (2008) model consisting of upstream and downstream analysis. The model is applied to PT Saraswati Griya Lestari, Tbk which manages five-star hotel. This research describes the value chain in the company from the upstream to the downstream side. Through the discussion of the application of the model, this study provides several alternative strategies that can be applied by the company. The research method used is case study which aims to present structured, factual, and accurate information about the object that is under study. The case study method is used to identify the value chain in the company engaging in hotel services through upstream activities up to the downstream side. This study uses SWOT analysis method to identify strategic strengths and weaknesses, as well as threats and opportunities that can be followed up by the company. This study identifies a number of strengths and weaknesses of firms based on (for example) corporate financial analysis. The results of the analysis are set forth in the IFAS and EFAS tables. Based on value chain analysis from upstream to downstream, the company allows to apply relevant strategies to the character of products and services offered by PT Saraswati Griya Lestari, Tbk. This study provides a managerial impact on the company that is under study, i.e. the company can apply the application of setting strategy to achieve company goals and can improve the components that are considered less.